PSMA-PET based radiotherapy: A review of initial experiences, survey on current practice and future perspectives - Zschaeck, Sebastian; Lohaus, Fabian; Beck, Marcus; Habl, Gregor; Kroeze, Stephanie; Zamboglou, Constantinos; Koerber, Stefan Alexander; Debus, Juergen; Hoelscher, Tobias; Wust, Peter; Ganswindt, Ute; Baur, Alexander D. J.; et al. (Radiation Oncology, 2018)
68Gallium prostate specific membrane antigen (PSMA) ligand positron emission tomography (PET) is an increasingly used imaging modality in prostate cancer, especially in cases of tumor recurrence after curative intended therapy. Owed to the novelty of the PSMA-targeting tracers, clinical evidence on the value of PSMA-PET is moderate but rapidly increasing. State of the art imaging is pivotal for radiotherapy treatment planning as it may affect dose prescription, target delineation and use of concomitant therapy. This review summarizes the evidence on PSMA-PET imaging from a radiation oncologist's point of view. Additionally a short survey containing twelve examples of patients and 6 additional questions was performed in seven mayor academic centers with experience in PSMA ligand imaging and the findings are reported here.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Image guided treatment planning; Primary radiotherapy; Prostate-cancer; PSMA-PET; Review; Salvage radiotherapy; Survey